2013
DOI: 10.1016/j.engstruct.2012.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Prestress losses evaluation in prestressed concrete prismatic specimens

Abstract: This paper presents an experimental research work to evaluate prestress losses in pretensioned 12 prestressed concrete. An experimental program including variables such as concrete mix 13 design, specimen cross-section size and concrete age at the prestress transfer was carried out. 14 Several pretensioned prestressed concrete prismatic specimens were made and tested using 15 the ECADA+ test method, based on measuring prestressing reinforcement force. In addition, 16 specimens were instrumented to obtain the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 15 publications
0
33
0
1
Order By: Relevance
“…Bymaster et al [89] studied prestress losses of light weight self-consolidating concrete and reported that current AASHTO design provisions [52] may overestimate elastic shortening loss for specimens with low concrete strength. Caro et al [90] and Garber et al [91] summarized the major prestress losses formulas and developed a database for pretensioned concrete structures.…”
Section: Immediate Prestress Lossesmentioning
confidence: 99%
“…Bymaster et al [89] studied prestress losses of light weight self-consolidating concrete and reported that current AASHTO design provisions [52] may overestimate elastic shortening loss for specimens with low concrete strength. Caro et al [90] and Garber et al [91] summarized the major prestress losses formulas and developed a database for pretensioned concrete structures.…”
Section: Immediate Prestress Lossesmentioning
confidence: 99%
“…Furthermore, almost all of the test specimens used in the previous studies were limited to small-scale concrete members [7][8][9]. There are a few reports on friction loss tests using full-scale concrete girders.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, extensive laboratory tests on pre-stress friction loss have been carried out. The Anchorage-Measurement-Access (AMA) system is the main experimental idea proposed for estimating the pre-stress friction loss [16]. Two full-scale pre-stressed concrete girders were constructed [17] and the influence at various pre-stress levels was discussed.…”
Section: Introductionmentioning
confidence: 99%